Gender Performativity as Asserted on Kate Chopin’s A Respectable Woman - Cahyaningsih Pujimahanani; Rommel Utungga Pasopati; Flora Anasis (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
Literature is colored with gender studies that emphasize female struggle through social construction. The understandings widen from equalities between male and female to how woman should define her self-identity. Identity through gender is not static at all, but dynamic through its process as examined by Judith Butler through her concept of gender performativity. A Respectable Woman is Kate Chopin’s short story that tells Mrs. Baroda who is disturbed with the presence of her husband’s friend, Gouvernail, at her home. She is tempted by him but she realizes that and leaves home. She returns home and speaks to her husband, Gaston that she has made up her mind and be ready if his friend will stay over again. Then, how is gender performativity asserted on Kate Chopin’s A Respectable Woman? Through qualitative method on cultural studies, this writing underlines the wife’s firm state for not being tempted as her own self-definition. It becomes usual for a woman to fall to other man, but the wife thinks differently. She is aware of being tempted and she avoids it. Her identity is not defined by common ideas or dictated by male dominations. She is herself with her own determination by being so earnest. In conclusion, the wife’s resolution to step back, to think, and to return to her husband is her approach to define her identity. This is in line with gender performativity that is stated in line with Chopin’s focus on female subjectivity.